Comparative Analysis of the Financial Performance of Banking Companies Before and After the Covid-19 Announcement: Analisis Perbandingan Kinerja Keuangan Perusahaan Perbankan Sebelum dan Sesudah Pengumuman Covid-19 - Hilda Melinda; Nurasik Nurasik (Academia Open, 2021)
This study aims to determine whether there are differences in Return On Assets (ROA), Return On Equity (ROE), Net Profit Margin (NPM) and Non Performing Loans (NPL) before and after the announcement of the COVID-19 pandemic in state-owned banking companies listed on the stock exchange. Indonesian effect. The research population includes all state-owned banking companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2020 period. The sampling technique used is purposive sampling. The sample data taken are BUMN banking companies listed on the Indonesia Stock Exchange as many as 4 BUMN banking companies listed on the IDX. The data analysis method used is the paired sample t test with SPSS for windows. The results of this study indicate: there are differences in Return On Assets (ROA) in banking companies between before and after the announcement of the Covid-19 pandemic, there are differences in Return On Equity (ROE) in banking companies between before and after the announcement of the Covid-19 pandemic, there are differences in Net Profit Margin (NPM) in banking companies between before and after the announcement of the Covid-19 pandemic, there is no difference in Non Performing Loans (NPL) in banking companies between before and after the announcement of the Covid-19 pandemic